2021
DOI: 10.1002/ajhb.23606
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of excess body weight and annual weight gain in women and men: Results from the ELSA‐Brasil cohort

Abstract: Objective: To estimate annual weight gain and the incidence of overweight and obesity, stratified according to gender and socioeconomic factors.Methods: From the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil), we included 13 625 women and men aged 35-74 (2008-2010) who attended a follow-up visit after a mean 3.8-years. Standardized questionnaires were used to record sociodemographic data, and height and weight were measured on all participants during in-person visits at research centers. The inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
2
0
2
Order By: Relevance
“…Obesity in postmenopausal women is significantly associated with a risk of breast cancer; however, none of the studies reported on women in this age group. Taking into account the tendency to remain obese over time and the poor success rate of weight loss programmes worldwide [68] , obesity during the reproductive years could represent a proxy for postmenopausal obesity [69] . These studies used different strategies to overcome a variety of methodological challenges, including difficulty in defining exposure with misreporting participation in programs leading to false negatives [53] , [70] .…”
Section: Discussionmentioning
confidence: 99%
“…Obesity in postmenopausal women is significantly associated with a risk of breast cancer; however, none of the studies reported on women in this age group. Taking into account the tendency to remain obese over time and the poor success rate of weight loss programmes worldwide [68] , obesity during the reproductive years could represent a proxy for postmenopausal obesity [69] . These studies used different strategies to overcome a variety of methodological challenges, including difficulty in defining exposure with misreporting participation in programs leading to false negatives [53] , [70] .…”
Section: Discussionmentioning
confidence: 99%
“…As proporções de sobrepeso e obesidade aumentaram com a idade, mais comumente entre aqueles com os menores níveis de renda per capita e menos anos de escolaridade. 376 …”
Section: Incidênciaunclassified
“…The proportions of overweight and obesity increased with age, more commonly among those with the lowest per capita income levels and fewer years of schooling. 376 …”
Section: Incidencementioning
confidence: 99%
“…Especificamente nos países da América Latina onde nota-se um aumento dos padrões alimentares inadequados e do sedentarismo, associados à desigualdade social, esta transição nutricional (da desnutrição para o excesso de peso) tem tomado proporções importantes rapidamente (3).…”
Section: Obesidadeunclassified